Preparation of 1,4-dihydropyridine Derivatives Using Perchloric Acid Adsorbed on Magnetic Fe3O4 Nanoparticles Coated with Silica - Mohammad Shafiee, Mohammad Reza; Ghashang, Majid; Fazlinia, Abbas (Current Nanoscience, 2013)
Perchloric acid adsorbed on magnetic Fe3O4 nano-particles coated with silica (Fe3O4@SiO2-HClO4) as a magnetically separable nano-catalyst was prepared and used for the preparation of 1,4-dihydropyridine derivatives via multi-component reaction of cinnamaldehyde, aromatic amines and methyl / ethyl acetoacetate in high yields. Quantitative conversion of the reactants was achieved under solvent-free conditions; recycle of the catalyst, through convenient magnetic decantation, shows non-significant loss in activity. The prepared nano-composite has been subjected for thorough characterization with X-ray diffraction (XRD) and Field Emission Scanning Electron Microscope (FE-SEM) techniques. The average particle size of nano-particles was obtained as 70 nm.
Keywords: Hantzsch reaction